2016
DOI: 10.1111/cen.13179
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of insulin autoimmune syndrome using polyethylene glycol precipitation and gel filtration chromatography withex vivoinsulin exchange

Abstract: SummaryContextInsulin‐binding antibodies may produce severe dysglycaemia in insulin‐naïve patients (‘insulin autoimmune syndrome’ (IAS) or Hirata disease), while rendering routine insulin assays unreliable.ObjectiveTo assess the performance of clinically used insulin assays and an optimal analytical approach in the context of IAS.DesignObservational biochemical study of selected patients with hyperinsulinaemic hypoglycaemia.PatientsThree patients without diabetes with recurrent spontaneous hyperinsulinaemic hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…Low insulin recovery following PEG precipitation using an immunoassay suggested IA. GFC with and without addition of exogenous human insulin showed predominantly high molecular weight (HMW) insulin immunoreactivity, confirming IAS ( 6 ). IAs were positive by ELISA and RIA, the latter indicating a high insulin-binding capacity.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…Low insulin recovery following PEG precipitation using an immunoassay suggested IA. GFC with and without addition of exogenous human insulin showed predominantly high molecular weight (HMW) insulin immunoreactivity, confirming IAS ( 6 ). IAs were positive by ELISA and RIA, the latter indicating a high insulin-binding capacity.…”
Section: Resultsmentioning
confidence: 64%
“…In this series, the first clue to IAS came from high insulin concentrations and insulin/C-peptide molar ratios in samples drawn during hypoglycemia. Immunoassay results were shown to be nonlinear to dilution at presentation (linearity improving following plasma exchange) and to underestimate MS-detected insulin in neat plasma, consistent with assay interference due to the IA competing with the immunoassay antibodies for insulin-binding sites ( 6 ). Consistent with previous observations ( 28–31 ), immunoassay C-peptide concentrations, in the five patients in whom they were measured, were reported at hundreds to thousands of picomoles per liter, concurrent with hypoglycemia.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Church and cols. demonstrated that immunoprecipitation with polyethylene glycol (PEG) must be used with caution in screening for insulinantibody complexes as gel filtration chromatography (GFC) with addition of exogenous insulin enhances sensitivity for the identification of insulin immunocomplexes (16). It is noteworthy that we did not consider the possibility of laboratory analytical interference, and we did not test heterophile antibodies.…”
Section: Discussionmentioning
confidence: 99%